2017
DOI: 10.4012/dmj.2016-355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium hydroxide reagent on the bond strength of resin cements to root dentin and the retention force of FRC posts

Abstract: The aim of this study was to determine the effects of calcium hydroxide (Ca(OH)2) treatment on bond strength of resin cements to root dentin and retention force of fiber-reinforced composite (FRC) posts. Bovine root dentin was endodontically prepared and treated with Ca(OH)2 for 7 days. Root dentin for bond strength test was adhered to resin-composite with resin cements. For pull-out test, posts consisting of FRC posts and resin-composites were fabricated and cemented to root. Shear bond and pull-out tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…On the other hand, there are conflicting results about the effect of CH, CHX, and DAP on bond strength of fiber post to dentin. 17 18 19 20 21 Considering the controversial results, this study sought to assess the effect of intracanal medicaments on pull-out bond strength of glass fiber post (Reforpost, Angelus, Brazil) cemented with dual-cured resin (Panavia F2, Kuraray, Tokyo, Japan)) to root dentin to evaluate the possible effects of intracanal medicaments on root dentin. The null hypothesis was that CH, CH and CHX, DAP, and TAP have no adverse effect on pull-out bond strength of glass fiber post.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are conflicting results about the effect of CH, CHX, and DAP on bond strength of fiber post to dentin. 17 18 19 20 21 Considering the controversial results, this study sought to assess the effect of intracanal medicaments on pull-out bond strength of glass fiber post (Reforpost, Angelus, Brazil) cemented with dual-cured resin (Panavia F2, Kuraray, Tokyo, Japan)) to root dentin to evaluate the possible effects of intracanal medicaments on root dentin. The null hypothesis was that CH, CH and CHX, DAP, and TAP have no adverse effect on pull-out bond strength of glass fiber post.…”
Section: Introductionmentioning
confidence: 99%
“…When the material comes into direct contact with vital tissue, a necrotic layer forms that acts as a precursor to mineralization, causing tissue dissolution and creating new granulation tissue that enters the perforation defect to promote wound healing. 34 Conflicting results have been reported regarding the effects of Ca(OH) 2 on the bond strength of fiber posts, with some studies reporting that the intracanal application of calcium hydroxide reduces bond strength, 18 others suggest that it increases bond strength, 19 and still others suggest that it has no effect 35 on bond strength. Both Lee et al 18 and Barbizam et al 36 have stressed the importance of completely removing Ca(OH) 2 from the canal prior to filling, as any residual Ca(OH) 2 may adversely affect the quality of the root filling and subsequent fiber post.…”
Section: Discussionmentioning
confidence: 99%
“…The retention force of FRC post to resin composite was evaluated with a pull-out test. Bond strength is usually evaluated through shear, push-out, or pull-out tests 21) . However, there are a number of limitations to evaluate the bond strength of FRC posts and the resin composite.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used pull-out tests to evaluate the retention of post and core on bovine teeth roots that underwent various surface treatments [21][22][23][24][25] . These studies reported that fractures occurred between the FRC post and resin composites [21][22][23][24][25] . Therefore, in this study, the retention force between the FRC post and resin composite was established as the maximum load during pull-out test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation